Development of a graphene-based surface plasmon resonance optical sensor chip for potential biomedical application - Sheh Omar, Nur Alia; Yap, Wing Fen; Saleviter, Silvan; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Anas, Nur Ain Asyiqin; Md Ramdzan, Nur Syahira; Roshidi, Mohammad Danial Aizad (MDPI, 2019)
The emergence of unintentional poisoning and uncontrolled vector diseases have contributed to sensor technologies development, leading to the more effective detection of diseases. In this study, we present the combination of graphene-based material with surface plasmon resonance technique. Two different graphene-based material sensor chips were prepared for rapid and quantitative detection of dengue virus (DENV) and cobalt ion (Co2+) as an example of typical metal ions. As the fundamental concept of surface plasmon resonance (SPR) sensor that relies on the refractive index of the sensor chip surface, this research focused on the SPR signal when the DENV and Co2+ interact with the graphene-based material sensor chip. The results demonstrated that the proposed sensor-based graphene layer was able to detect DENV and Co2+ as low as 0.1 pM and 0.1 ppm respectively. Further details in the detection and quantification of analyte were also discussed in terms of sensitivity, affinity, and selectivity of the sensor.